Pemanfaatan Bawang Putih dan Daun Pandan sebagai Pengawet Alami Tahu Ditinjau dari Masa Simpan dan Tingkat Kesukaan - Nur Cholifah; Lilik Hendrarini; Choirul Amri (Poltekkes Kemenkes Yogyakarta, 2017)
Tofu is a very popular food among the society. However, tofu is easily damaged (rotten) be-cause in normal condition (room temperature) the durability is in average of only 1-2 days. More than those days, tofu’s taste will be sour and gradually will decay, and therefore no longer con-sumable. So that, tofu maker often trying to add harmful preservatives such as formalin to extend the shelf life of tofu. Garlic and pandan leaves are natural preservatives alternative that is ex-pected can extend the shelf life of tofu but keep the taste still to be liked by the society. The ob-jective of this study was to identify the difference about the shelf life and the taste of tofu that was soaked in mixture solution of 2,5 % garlic and 2,5 % pandan leaves with those that was soaked in mineral water. Type of this research is a quasi-experiment with post-test only control group design. As the study object was 1440 pieces white tofu sized of 2 cm x 2 cm x 2,5 cm for 16 replications. The shelf life was measured by using ESS method based on organoleptic test, meanwhile the favour level based on tofu taste was gained from five panelists who observe the changing every 12 hours. Since the Shapiro-Wilk test stated that the data were not normally dis-tributed, so the further statistical analysis used Mann-Whitney test, and obtained p-values less than 0,001, which can be concluded that the the shelf life and the tase of tofu soaked in the solu-tion mixture of 2,5 % garlic and 2,5 % pandan leaves with tofu that was soaked in mineral water were significantly different. The duration of shelf life of tofu experiment was 23,3 hours longer than that of tofu control and the taste was also more favorable.